Deformation of the Pacific/North America plate boundary at Queen Charlotte Fault : the possible role of rheology - ten Brink, Uri S.; Miller, Nathaniel C.; Andrews, Brian D.; Brothers, Daniel S.; Haeussler, Peter J. (Journal of Geophysical Research: Solid Earth, 2018)
Published 2018. This article is a U.S. Government work and is in the public domain in the USA. The definitive version was published in Journal of Geophysical Research: Solid Earth 123 (2018): 4223-4242, doi:10.1002/2017JB014770. The Pacific/North America (PA/NA) plate boundary between Vancouver Island and Alaska is similar to the PA/NA boundary in California in its kinematic history and the rate and azimuth of current relative motion, yet their deformation styles are distinct. The California plate boundary shows a broad zone of parallel strike slip and thrust faults and folds, whereas the 49‐mm/yr PA/NA relative plate motion in Canada and Alaska is centered on a single, narrow, continuous ~900‐km‐long fault, the Queen Charlotte Fault (QCF). Using gravity analysis, we propose that this plate boundary is centered on the continent/ocean boundary (COB), an unusual location for continental transform faults because plate boundaries typically localize within the continental lithosphere, which is weaker. Because the COB is a boundary between materials of contrasting elastic properties, once a fault is established there, it will probably remain stable. We propose that deformation progressively shifted to the COB in the wake of Yakutat terrane's northward motion along the margin. Minor convergence across the plate boundary is probably accommodated by fault reactivation on Pacific crust and by an eastward dipping QCF. Underthrusting of Pacific slab under Haida Gwaii occurs at convergence angles >14°–15° and may have been responsible for the emergence of the archipelago. The calculated slab entry dip (5°–8°) suggests that the slab probably does not extend into the asthenosphere. The PA/NA plate boundary at the QCF can serve as a structurally simple site to investigate the impact of rheology and composition on crustal deformation and the initiation of slab underthrusting.